Screening of Probiotic Candidates in Human Oral Bacteria for the Prevention of Dental Disease - Terai, Tomohiko (PLoS One, 2015)
The oral cavity in healthy subjects has a well-balanced microbiota that consists of more than 700 species. However, a disturbance of this balance, with an increase of harmful microbes and a decrease of beneficial microbes, causes oral disorders such as periodontal disease or dental caries. Nowadays, probiotics are expected to confer oral health benefits by modulating the oral microbiota. This study screened new probiotic candidates with potential oral health benefits and no harmful effects on the oral cavity. We screened 14 lactobacillus strains and 36 streptococcus strains out of 896 oral isolates derived from healthy subjects. These bacteria did not produce volatile sulfur compounds or water-insoluble glucan, had higher antibacterial activity against periodontal bacteria, and had higher adherence activity to oral epithelial cells or salivary-coated hydroxyapatite in vitro. We then evaluated the risk of primary cariogenicity and infective endocarditis of the selected oral isolates. As a result, Lactobacillus crispatus YIT 12319, Lactobacillus fermentum YIT 12320, Lactobacillus gasseri YIT 12321, and Streptococcus mitis YIT 12322 were selected because they showed no cariogenic potential in an artificial mouth system and a lower risk of experimental infective endocarditis in a rat model. These candidates are expected as new probiotics with potential oral health benefits and no adverse effects on general health.